Testing the Teacher's Report Form Syndromes in 20 Societies - Ivanova, M.; Achenbach, T.; Rescorla, L.; Dumenci, L.; Almqvist, F.; Bathiche, M.; Bilenberg, N.; Bird, H.; Domuta, A.; Erol, N.; Fombonne, E.; Fonseca, A.; et al. (National Association of School Psychologists, 2007)
Standardized assessment instruments developed in one society are often used in other societies. However, it is important to determine empirically how assessment instruments developed in one society function in others. The present study tested the fit of the Teacher's Report Form syndrome structures in 20 diverse societies using data for 30,030 6- to 15-year-old students from Asia; Australia; the Caribbean; eastern, western, southern, and northern Europe; and the Middle East. A correlated seven-syndrome model and a hierarchical Attention Problems model were tested separately in each of the 20 societies via confirmatory factor analyses. The results supported the fit of the models in the tested societies.